Chloroplast-Localized Protoporphyrinogen IX Oxidase1 Is Involved in the Mitotic Cell Cycle in Arabidopsis. (26th July 2019) - Li, Jialong; Zhang, Fan; Li, Yuhong; Yang, Weicai; Lin, Rongcheng
Abstract: Protoporphyrinogen IX oxidase1 (PPO1) catalyzes the oxidation of protoporphyrinogen IX to form protoporphyrin IX in the plastid tetrapyrrole biosynthesis pathway and is also essential for plastid RNA editing in Arabidopsis thaliana . The Arabidopsis ppo1-1 mutation was previously shown to be seedling lethal; however, in this study, we showed that the heterozygous ppo1-1/+ mutant exhibited reproductive growth defects characterized by reduced silique length and seed set, as well as aborted pollen development. In this mutant, the second mitotic division was blocked during male gametogenesis, whereas female gametogenesis was impaired at the one-nucleate stage. Before perishing at the seedling stage, the homozygous ppo1-1 mutant displayed reduced hypocotyl and root length, increased levels of reactive oxygen species accumulation and elevated cell death, especially under light conditions. Wild-type seedlings treated with acifluorfen, a PPO1 inhibitor, showed similar phenotypes to the ppo1-1 mutants, and both plants possessed a high proportion of 2C nuclei and a low proportion of 8C nuclei compared with the untreated wild type. Genome-wide RNA-seq analysis showed that a number of genes, including cell cycle-related genes, were differentially regulated by PPO1. Consistently, PPO1 was highly expressed in the pollen, anther, pistil and root apical meristem cells actively undergoing cell division. Our study reveals a role for PPO1 involved in the mitotic cell cycle during gametogenesis and seedling development.